Electrostatic self-assembly of citrus based carbon nanosheets and MXene: Flexible film electrodes and patterned interdigital electrodes for all-solid supercapacitors. (February 2023) - Zhang, Shuai; Huang, Ying; Ruan, Yifeng; Wang, Jiaming; Han, Xiaopeng; Sun, Xu
Abstract: Lightweight, flexible, patterned, and environmentally friendly electronic devices should be developed to meet the requirements of future high-tech systems such as smart wearables, internet of things and smart cities. Herein, MXene and citrus-based carbon nanosheet composites (MX/CCNS) with excellent energy storage properties and cyclic stability are prepared via electrostatic self-assembly. MX/CCNS can be easily fabricated as flexible self-supporting electrodes by vacuum filtration and configured as ink for screen printing and large-scale continuous preparation of patterned electrodes. MX/CCNS film electrodes have high specific capacitance (up to 1825.6 mF/cm 2 at a current density of 5 mA/cm 2 ) and high cycling stability (99.82% capacity retention after 10, 000 cycles). Meanwhile, MX/CCNS can be assembled into flexible all-solid-state and interdigital devices, all exhibiting excellent capacitive performance. The capacitance (114.9 mF/cm 2 ) and energy density (12.9 μWh/cm 2 ) of the printed interdigital supercapacitors are competitive among MXene-based devices. MX/CCNS has great application prospects in scalable and sustainable production of next-generation wearable intelligent electronics. Graphical abstract: Unlabelled Image Highlights: Ti3 C2 Tx MXene and citrus-based carbon nanosheets (CCNS) were combined by means of electrostatic self-assembly. The insertion of CCNS enhances the capacitive performance of the material. The MX/CCNS was fabricated into flexible self-supporting electrodes by vacuum filtration and assembled into an ultra-thin, high-performance all-solid-state supercapacitor. MX/CCNS composite was made into addictive-free ink for screen printing to prepare patterned interdigital devices that are easy to be connected in series. Excellent performance was obtained.